A SPATIAL EVALUATION OF THE IMPACT OF AIR POLLUTION: A GIS-BASED APPROACH - Špeh, Natalija; Barborič, Blaž; Kopušar, Nataša (Journal of Energy Technology, 2024)
The common denominator of the three areas discussed in this paper is basin-type terrain; all areas of the research were thoroughly transformed by human activities (mining, production of energy,industry, settlements and associated infrastructure) in the second half of the 20th century:1) the wider area of Plevlja Community in Montenegro; air quality indicators were monitored at 19 sampling places;2) Tuzla basin in Bosnia and Herzegovina as a heavily polluted landscape (industry, energy production, heating of private furnace); 20 monitoring sites were placed there. The anthropogenic environmental pressures have not been reduced;3) Šalek Valley (Slovenia) as an example with an entire range of well-established technological environmental solutions and measures in the manufacturing sector with 34 measuring points.In all three cases, very active transport activity caused by different users represents significant environmental pressure. The evaluation of the quality of the living environment was made indirectly, using theenvironmental indicator method. The basis of the survey was carried out during the winter heating period, since we intended to determine the presence of some air pollutants and their effects (especially spatial ones) on the quality of the living environment. Principally, the researched areas are more delicate in the winter period, because private heating system fossil fuels are used. We monitored sulphur dioxide and nitrogen dioxide. In the survey, the method of measurement with diffusion tubes placed at various outdoor locations of the living environment was used, with locations in rural and urban area.We wanted to add an applied value to the preliminary results of measurements, so these results were used for the spatial presentation below. Both can play an important role in the municipal spatial planning of socio-economic activities, e.g. settlement, educational and medical institutions, manufacturing facilities. Furthermore, we intend to show the obtained results of the air quality level in relation to the data on morbidity in the treated areas, i.e. cardiorespiratory diseases.